Evaluation of an interactive e-learning module "Toothache Clinic" for delivering information on dental pain: a prospective cohort study - Maria Giraki; Michael Kann; Puria Parvini; Karina Obreja; Tugba Zahn; Stefan Rüttermann; Susanne Gerhardt-Szep (Open Journal of Pain Medicine - Peertechz Publications, 2018)
This multivariate, prospective, monocentric, observational study evaluates the experimental application of an interactive e-learning module on the topic of dental pain, which deals with the content of interdisciplinary diagnostics and therapy of dental pain. The module ("Toothache Clinic") was offered to dentistry students during the first, second and fourth clinical semesters. A total of n = 138 students took part.  The questionnaire used in the study comprised 43 items (assigned to three domains) as well as questions on academic progress, gender, information technology (IT) background and module evaluation. The explorative factor analysis resulted in a reliability value (Cronbach's Alpha) of 0.94. The results show a good rating for the module of 2.09 ± 0.55 (1 = excellent to 6 = unsatisfactory) across all groups. 94.17% of the volunteers would recommend the module to their fellow students. With a rating of 1.96 ± 0.51 (1 = excellent to 6 = unsatisfactory), women rated the module significantly better than men who rated it 2.27± 0.67 (p = 0.016). There were no significant differences in the ratings of the module between the three semesters. Furthermore, the results show no significant correlation between module assessment and prior information concerning technology education. In summary, it can be said that the students rated the e-learning module ("Toothache Clinic") positively, regardless of their IT (information technology) knowledge and academic progress.  Keywords: pain medicine, dental, e-learning, gender, education